2019
DOI: 10.1039/c8sc01959b
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic modulation of the charge distribution in a metal–organic framework for optimal binding of carbon dioxide and sulfur dioxide

Abstract: Modulation of pore environment is an effective strategy to optimize guest binding in porous materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 49 publications
(63 reference statements)
3
45
0
1
Order By: Relevance
“…176 Initial results show that trivalent Al 3+ and In 3+ carboxylate frameworks reversibly bind dry SO2 in static adsorption experiments. [177][178][179] The Al 3+ carboxylate MOFs, MFM-305-CH3, MFM-305, and MFM-300 (née NOTT-300) all reversibly adsorb SO2 with high capacities above 5 mmol g -1 . 178,179 In situ powder X-ray diffraction analysis on MFM-300 revealed that SO2 strongly interacts with the bridging hydroxyl groups of the SBU.…”
Section: Mofs For So 2 Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…176 Initial results show that trivalent Al 3+ and In 3+ carboxylate frameworks reversibly bind dry SO2 in static adsorption experiments. [177][178][179] The Al 3+ carboxylate MOFs, MFM-305-CH3, MFM-305, and MFM-300 (née NOTT-300) all reversibly adsorb SO2 with high capacities above 5 mmol g -1 . 178,179 In situ powder X-ray diffraction analysis on MFM-300 revealed that SO2 strongly interacts with the bridging hydroxyl groups of the SBU.…”
Section: Mofs For So 2 Adsorptionmentioning
confidence: 99%
“…[177][178][179] The Al 3+ carboxylate MOFs, MFM-305-CH3, MFM-305, and MFM-300 (née NOTT-300) all reversibly adsorb SO2 with high capacities above 5 mmol g -1 . 178,179 In situ powder X-ray diffraction analysis on MFM-300 revealed that SO2 strongly interacts with the bridging hydroxyl groups of the SBU. 178 Moving to the more labile In 3+ , NOTT-202a [In(O2CR)4] (O2CR = biphenyl-3,3,5,5-tetra-(phenyl-4-carboxylate)) reversibly binds SO2 with an adsorption capacity of 10 mmol g -1 at 1 bar and temperatures between 293-303 K. 177 However, low temperature (268-283 K) SO2 adsorption isotherms feature hysteretic adsorption of an additional 2-6 mmol SO2 g -1 as a consequence of an irreversible phase change to form a denser crystalline polymorph.…”
Section: Mofs For So 2 Adsorptionmentioning
confidence: 99%
“…Porous metal-organic frameworks (MOFs) have been studied extensively for uptake and separation of a wide variety of gases, notably CO 2 , H 2 and hydrocarbons, 9-adsorbents ( Table 1, Fig 2), [15][16][17][18][19][20][21][22][23][24][25] but many exhibit limited stability and/or reversibility under near-ambient conditions. Current top-performing MOFs for SO 2 adsorption at 298 K and 1.0 bar include MFM-202a (10.2 mmol g -1 ) 18 and SIFSIX-1-Cu (11.0 mmol g -1 ) 16 .…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Developments in gas-handling systems have also paved the way to probe gate-opening and related network-breathing phenomena arising from the unique elastic properties of MOFs—see entries in Table 1 and Refs. [ 151 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: From Confined Polymers To Soft Supramolecular Frameworkmentioning
confidence: 99%